Conservation tillage to peanut crop in rotation with green harvest sugarcane - Bolonhezi, Denizart; Mutton, Miguel Ângelo; Martins, Antonio Lúcio Mello (Pesquisa Agropecuaria Brasileira, 2007)
Field studies were conducted from 2000 to 2005 to evaluate the effects of conservation tillage on agronomic characteristics of two peanut cultivars, cultivated in rotation with sugarcane harvested without burning. Tillage systems included reduced tillage, no-tillage, and conventional tillage, which were arranged in a split-plot randomized complete block design with four replications in two different types of soil, Oxisol and Ultisol, located in Ribeirão Preto and Pindorama cities, SP, Brazil. Tillage treatments were main plots while subplots were peanut genotypes (IAC-Tatu ST and IAC-Caiapó). Results of seven experiments showed no statistic difference on pod yield, kernel yield, number of pods and pegs, between the conservation tillage systems and the conventional tillage, but a decrease on stand of plants can occur. Three out of seven experiments showed a significant interaction between the cultivar and tillage system. The response of different tillage systems for cv. IAC-Caiapó was lower than for cv. IAC-Tatu ST. No-tillage system can show increase (between 6.5 and 9%) on mature kernel rate as well as good or better soil moisture during a dry period.